A concepção de gestão da escola municipal de educação infantil e ensino fundamental Professora Odaléa Maués Quaresma - BITENCOURT, Joyce Barreto (2022)
This course conclusion work aims to bring results from the research project “The management conception of the Municipal School of Early Childhood Education and Elementary Education Professora Odaléa Maués Quaresma”. The present work has as general objective, based on the historical trajectory of school administration in Brazil and the identification and description of the main management concepts, to identify which management conception(s) guides the actions of the Municipal School of Early Childhood Education and Elementary School Teacher Odaléa Maués Quaresma. And as specific objectives, describe the course of administration/school management in Brazil, identifying the main conceptions, and identify which was the main conception of management diagnosed in the school. The research is social, thus, it has a qualitative approach, the technique used was document analysis. The results identify that the main conception of school management is participatory democratic, as the school encourages the participation of the school community and also has a school council, whose basic function is to democratize power relations, but there are remnants of ideas technical-scientific, as the school is regulated by a bureaucratic educational system.